Les mécanismes d'application de la Charte sociale européenne - Aubert, Gabriel (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1985)
Less well known than its predecessor the 1950 European Convention on Human Rights, the European Social Charter that came into force in October 1965 is no less a fundamental piece of European international law that is of interest to evaluate. Perhaps precisely because of the nature of its object, the Charter, as it would seem, has operational and concrete application difficulties that the Convention does not have.